Stock market reaction to increased transparency: An analysis of country-by-country reporting in developing countries - Bathusi Gabanatlhong (Charles University in Prague, Institute of Economic Studies (IES), 2024)
Country-by-country reporting aims to curb tax avoidance by multinational corporations and increase transparency in the tax system. This paper provides the first evidence of the effect of country-by-country in developing countries, focusing on the market response of the African stock market to this regulation. Using an event study design, the results indicate a significant negative market response for firms subject to CbCR requirements. Tax-aggressive firms show a pronounced significant negative response around the event date, suggesting that investors anticipate increased tax liabilities due to heightened scrutiny of their tax planning practices, potentially reducing future profits. Cross-listed firms exhibit a positive significant market response in foreign markets, while the broader domestic market shows a negative reaction, underscoring the variation in how foreign and domestic investors process similar information. This paper sheds light on how regulatory transparency influences investor sentiment across different markets.
Keywords: F23; H25; H26; G14; 330; country-by-country reporting; developing countries; event study; cross-listed firms; heterogeneous treatment effect; generalised random forest